Mismatch discrimination in fluorescent in situ hybridization using different types of nucleic acids - Sílvia Fontenete (2015)
In the past few years, several researchers have focused their attention on nucleic acid mimics due to the increasing necessity of developing a more robust recognition of DNA or RNA sequences. Fluorescence in situ hybridization (FISH) is an example of a method where the use of these novel nucleic acid monomers might be crucial to the success of the analysis. To achieve the expected accuracy in detection, FISH probes should have high binding affinity towards their complementary strands and discriminate effectively the noncomplementary strands. In this study, we investigate the effect of different chemical modifications in fluorescent probes on their ability to successfully detect the complementary target and discriminate the mismatched base pairs by FISH. To our knowledge, this paper presents the first study where this analysis is performed with different types of FISH probes directly in biological targets, Helicobacter pylori and Helicobacter acinonychis. This is also the first study where unlocked nucleic acids (UNA) were used as chemistry modification in oligonucleotides for FISH methodologies. The effectiveness in detecting the specific target and in mismatch discrimination appears to be improved using locked nucleic acids (LNA)/2′- O-methyl RNA (2′OMe) or peptide nucleic acid (PNA) in comparison to LNA/DNA, LNA/UNA, or DNA probes. Further, the use of LNA modifications together with 2′OMe monomers allowed the use of shorter fluorescent probes and increased the range of hybridization temperatures at which FISH would work.